2013
DOI: 10.1080/00071668.2013.791385
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TRPV6 and CaBP-D28k in the egg shell gland (uterus) during the oviposition cycle of the laying hen

Abstract: 1. The aim of this study was to investigate the localisation of the transient receptor potential vanilloid channel type 6 (TRPV6) in egg shell gland (ESG) and examine the dynamic expression of TRPV6 and Calbindin-d28k (CaBP-D28k), as well as the changes in concentration of total calcium (Ca), total inorganic phosphorus (P), alkaline phosphatase (ALP), parathyroid hormone (PTH) and calcitonin (CT) in plasma during the oviposition cycle. 2. The plasma ALP activity was notably increased at 8 h. In addition, plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…These two proteins have been observed in the oviduct of birds, but their functional properties are poorly understood. CALB1 is present in the cytosol of gland cells of the uterus at high concentration (Jande et al, 1981), and strong TRPV6 immunostaining is found specifically in the apical regions of the luminal epithelium of the uterus (Yang et al, 2013). These findings generally agreed with our results, but we also observed CALB1 in the normal uterine epithelium and TRPV6 throughout the cytoplasm of the gland cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These two proteins have been observed in the oviduct of birds, but their functional properties are poorly understood. CALB1 is present in the cytosol of gland cells of the uterus at high concentration (Jande et al, 1981), and strong TRPV6 immunostaining is found specifically in the apical regions of the luminal epithelium of the uterus (Yang et al, 2013). These findings generally agreed with our results, but we also observed CALB1 in the normal uterine epithelium and TRPV6 throughout the cytoplasm of the gland cells.…”
Section: Discussionsupporting
confidence: 92%
“…Because Japanese quail are not commonly used as experimental animals, we could not obtain species-specific target proteins and could not examine the reactivities of these primary antibodies in quail. However, the cross-reactivity of the CALB1 antibody against its target protein in chickens has been confirmed by its manufacturer, and immunostaining of chicken tissues with TRPV6 antibody has been reported previously (Yang et al, 2013). We found here that the CALB1, SPP1, and TRPV6 antibodies immunostained specific regions of the quail uterus; as described in the DISCUSSION, the respective proteins are located similarly in chickens.…”
Section: Histopathology and Immunohistochemistrysupporting
confidence: 87%
See 1 more Smart Citation
“…CT may, however, have a greater role than presently accepted in situations of calcium stress such as during pregnancy or lactation in mammals 100 or during egg shell calcification in birds. 102 Parathyroid glands first appeared during evolution in amphibians but PTH genes are widely expressed in most tissues of fish. 90 PTH receptors are older and were already used for signaling of PTHrP, which functions as a major paracrine factor 103 and can also act as a hypercalcemic factor in early vertebrates.…”
Section: Pth Sibling Proteinsmentioning
confidence: 99%
“…Evidence is accumulating that the surface epithelium provides the bulk of the Ca 2+ needed for shell formation [37,38]. The latest finding supporting this is the localization of transient receptor potential vanilloid channel type 6 (TRPV6) to the apical surface of these cells and that its mRNA increases in the shell gland during shell formation [39]. Since estrogen increases TRPV6 in human uterus [12] this is a very interesting candidate for future studies to elucidate the effects of estrogen on shell gland function.…”
Section: Discussionmentioning
confidence: 99%